Tratamiento de aguas contaminadas con amoxicilina mediante el proceso de oxidación con dióxido de cloro - Quino Quispe, Nexon (2024)
The objective of this research was to determine the degree of degradation of Amoxicillin in polluted waters through the oxidation process with chlorine dioxide (ClO2). For this process, the pH (5, 6.5 and 8) and thedose of ClO2 (5, 12.5 and 20 ml) variables were studied in 47.20 ppm samples of amoxicillin in 500 mL volumes, this process was carried out in a jars-test. The results indicate that the two variables (pH and ClO2 dose) have an important effect and are significant on the percentage of eliminated Chemical Oxygen Demand (%DQOe). The mathematical model that relates the variables under study was established with a goodness of fit equal to R2 = 99.68%. Likewise, a removal of 77.3% was achieved at pH8 and a ClO2 dose of 20 mL.